Long Non-Coding RNAs Emerging as Potential Epigenetic Biomarkers for Tobacco and/or Alcohol-Induced Head and Neck Cancer - Gupta Shilpi; Kumar Prabhat; Maini Jayant; Bharadwaj Mausumi (Journal of Cancer Genetics And Biomarkers, 2019)
Head and Neck cancer (HNC) is one of the most prevalent and lethal cancer globally. The incidence of tobacco-induced HNC is gradually increasing in low and middle income countries. Among the various causative factors associated with HNCs, tobacco and alcohol play synergistic effect and are frequently associated with the risk of HNC. Tobacco-induced HNCs show distinct genetic and epigenetic alterations leading to different clinical outcomes in comparison to HPV-infected HNCs. Tobacco-induced HNCs are often associated with tumor aggressiveness, poor prognosis and low or nil prevalence of HPV infection. Apart from carcinogenic effects of these causative factors (use of tobacco products, alcohol intake and HPV or EBV infections), recent studies show that exposure to these factors alter/disrupt the regulation of non-coding RNAs including the long non-coding RNAs (lncRNAs). Altered lncRNA regulation is brought about by signalling networks that regulate cellular differentiation, apoptosis, angiogenesis and inflammatory pathways which play key functions in the genesis of different cancers including HNCs. There are numbers of studies supporting the emerging role of lncRNAs in development of HNC; however, reports connecting lncRNAs expression and addiction habits in HNC are still preliminary and sparse. Therefore, identification and characterization of lncRNAs that are differentially expressed upon exposure to risk-factors can serve as unique therapeutic targets and potential biomarker(s) for effective treatment of HNC subtypes. In this short review, we briefly reviewed the emerging role of lncRNAs in tobacco and alcohol induced HNCs.
Keywords: HNC